2005
DOI: 10.1175/jhm-398.1
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variability of Evapotranspiration in California

Abstract: The variability (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) of potential evapotranspiration estimates (ETo) and related meteorological variables from a set of stations from the California Irrigation Management System (CIMIS) is studied. Data from the National Climatic Data Center (NCDC) and from the Department of Energy from 1950 to 2001 were used to validate the results. The objective is to determine the characteristics of climatological ETo and to identify factors controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 36 publications
(39 reference statements)
0
33
2
2
Order By: Relevance
“…One relatively large group of model projections that was recently examined for California provides a range of about 2.5 to 9 degrees Celsius temperature rise for Northern California by 2100. An analysis of the distribution of the projections generally showed a central tendency at about 3 degrees Celsius of rise for 2050, and about 5 degrees Celsius for 2100 (Dettinger, 2005).…”
Section: Temperature Projectionsmentioning
confidence: 93%
See 2 more Smart Citations
“…One relatively large group of model projections that was recently examined for California provides a range of about 2.5 to 9 degrees Celsius temperature rise for Northern California by 2100. An analysis of the distribution of the projections generally showed a central tendency at about 3 degrees Celsius of rise for 2050, and about 5 degrees Celsius for 2100 (Dettinger, 2005).…”
Section: Temperature Projectionsmentioning
confidence: 93%
“…In the next section about energy budget the relationships between climatic factors are discussed along with relative influences they exert. Although Hidalgo et al (2005) concluded that to maintain ET o in the current condition requires a decrease in R n of about 6 percent to compensate for a temperature increase of 3ºC, they did not account for increased stomatal resistance that is likely to result from higher CO 2 concentration, which is discussed in detail later in this chapter. Hidalgo et al were clearly correct in that the effects of climate change on ET o are difficult to forecast because of the uncertainty of cloud cover and relative humidity.…”
Section: -2mentioning
confidence: 98%
See 1 more Smart Citation
“…56 (Allen et al, 1998). The CIMIS Penman equation, described in detail in Hidalgo et al (2005) (see http://wwwcimis.water.ca.gov/cimis/ infoEtoCimisEquation.jsp), is:…”
Section: Estimation Of the Pomona And Santa Monica Station Et 0 Datamentioning
confidence: 99%
“…56 (Allen et al, 1998). The CIMIS Penman equation is also described in detail in Hidalgo et al (2005) …”
Section: Estimation Of Et 0 Data Of the Pomona Stationmentioning
confidence: 99%